Reassessment of Islamic Legal Bases for Matrimonial Property in Malaysia - Jusoh Yusoff, Amir Fazlim (El-Usrah: Jurnal Hukum Keluarga, 2024)
Most Islamic countries do not implement laws related to matrimonial property (harta sepencarian). This is due to the absence of specific provisions in the Quran and hadith that permit such practices. However, Malaysia has long practiced this and has a comprehensive legal framework concerning matrimonial property. Given this, is the practice in Malaysia truly in line with the teachings of the Quran and hadith? Therefore, this study aims to revisit the foundations of Islamic law regarding the implementation of matrimonial property laws. This research adopts Islamic normative legal research based on the principles of usul al-fiqh. This study reveals that the legal foundations cited by proponents of matrimonial property implementation, which include 'urf, syirkah, istishab and maslahat mursalah are inaccurate and do not align with the principles of usul al-fiqh. Thus, a new principle or legal basis is needed to legitimize Islamic matrimonial property distribution in Malaysia.